Parametric instability influence on isotope separation by ion-cyclotron resonance method - Olshansky, V.V.; Stepanov, K.N. (Вопросы атомной науки и техники, 2006)
Solution of the dispersion equation for linear potential ion cyclotron oscillations with characteristic parameters used
for selective ion cyclotron resonance separation of gadolinium isotopes has revealed the presence of the shortwavelength
unstable oscillation in the ion cyclotron frequency range. Computer simulation of this instability by means
of macro particle technique has shown that this instability may be responsible for turbulent heating of both resonant and
nonresonant ions obtaining large transversal energy. It can decrease the efficiency of this method.